2022
DOI: 10.1097/icb.0000000000001040
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Checkpoint Inhibitors in Paraneoplastic Acute Exudative Polymorphous Vitelliform Maculopathy: Report of Two Cases

Abstract: We hypothesize that nivolumab, an immune checkpoint inhibitor, can provoke paraneoplastic acute exudative polymorphous vitelliform maculopathy by means of a tumoral immune reaction with cross-reaction against the retinal pigment epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…When nivolumab was reinitiated the patient simultaneously underwent a surgical resection of the primary tumor. This combination was accompanied by a significant reduction of the subretinal fluid [8]. Compared to our case, their shorter immune checkpoint inhibitor free period could partly explain why little improvement was seen.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…When nivolumab was reinitiated the patient simultaneously underwent a surgical resection of the primary tumor. This combination was accompanied by a significant reduction of the subretinal fluid [8]. Compared to our case, their shorter immune checkpoint inhibitor free period could partly explain why little improvement was seen.…”
Section: Discussioncontrasting
confidence: 49%
“…Miyamoto et al reported a case describing multiple bilateral serous retinal detachments and outer segment thickening without inflammation in a patient treated with the PD-1 immune checkpoint inhibitor nivolumab [3]. Kemels et al hypothesized that nivolumab indirectly provoked paraneoplastic AEPVM [8]. Harpal et al presented a case of a patient with AEPVM during vemurafenib and pembrolizumab treatment for metastatic melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The exact underlying pathophysiology is not yet fully understood, but molecular mimicry is the globally accepted mechanism. Presumably, the increased antitumor response induced by ICI leads to an increased cross-reaction of antibodies against non-tumor antigens; namely against the Retinal Pigment Epithelium (RPE) in pAEPVM, against bipolar cells in MAR, and against photoreceptors in CAR [15,22,23,[29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The search strategy yielded nine cases of pAEPVM related to ICI (ipilimumab n=4, nivolumab n=3, pembrolizumab n=2) [21][22][23][24][25][26][27][28]. The mean age was 62.8 years (range 46 -78).…”
Section: Paepvmmentioning
confidence: 99%
“…16 6 reports were excluded because visual symptoms or ocular findings were reported prior to the initiation of immunotherapy. 6 17-21 14 patients from 13 reports were included in the review [22][23][24][25][26][27][28][29][30][31][32][33][34]…”
Section: Casementioning
confidence: 99%